Washing our hands in the clouds : Joe Williams, his forebears, and Black farms in South Carolina - Petersen, Bo, 1955- (The University of South Carolina Press, 2015)
"In Washing Our Hands in the Clouds, Bo Petersen masterfully crafts a reflection on the Civil War, emancipation, Jim Crow, and the civil rights movement in the personal story of how it affected one man's life in a specific South Carolina locale. Petersen's accomplishment is that, in studying the Pee Dee region of Dillon and Marion Counties, he illuminates those issues throughout the Deep South. Through conversations with Joe Williams, his family, and acquaintances, white and black, Petersen merges the Williams family history back to Joe's great-great-grandfather, Scipio Williams, with the lives and fortunes of four generations of South Carolinians--black and white. Scipio, the family progenitor, was a man free in spirit and action before the Civil War destroyed chattel slavery. Scipio was a free black farmer who worked land that he owned in the Pee Dee before and after the war and during the worst days of Jim Crow white supremacy. Petersen uses the Williams family genealogy, neighborhood, and, most important, their farmlands to understand Pee Dee and South Carolina history from the 1860s to the present. In his research he discovers historical currents that run deeper than events--currents of agriculture, land ownership, and allegiance to native soil--and transcend the march of time and carry the Williams family through slavery, war, Jim Crow, and economic dislocation to today's stories of Joe Williams. In gathering what Petersen describes as a collection of front porch stories, he also writes a history of what matters most to this family and this locale. The resulting narrative is surprising, unconventional, and true for all families in all places. In Dillon County, tobacco production followed cotton farming. Old-time logging coexisted with textile factories. Jim Crow gave way to uncertain prospects of racial harmony. Those were monumental changes of circumstance, but they did not change human character. Washing Our Hands in the Clouds is a history of human character, of life that endures outside of the restraints of time. To understand this phenomenon is to realize that both Scipio and Joe and the generations between them wash their hands in the timeless clouds of South Carolina's sky"--